Comparison of mothers’ perceptions of hunger cues in 3-month-old infant under different feeding methods - Fenghua Zhao; Yijie Sun; Yue Zhang; Tao Xu; Nianrong Wang; Shuangqin Yan; Ting Zeng; Fenghua Zhang; Jie Gao; Qing Yue; Scott Rozelle (BMC Public Health, 2023)
Abstract Background Mothers’ perception of infant hunger cues is a critical content of responsive feeding, which is central to the promotion of early childhood development. However, only a few studies have examined responsive feeding in China, especially lacking the studies on perceptions of infant hunger cues. Consider the cultural differences, the aim of this study was to describe the perceptions of infant hunger cues of Chinese mothers for infants aged 3 months, and explore the relationship between maternal perceptions of infant hunger cues and different feeding methods. Methods A cross-sectional study was conducted with a sample of 326 mothers of healthy 3-month-old infants, including 188 exclusive breastfeeding (EBF) mothers and 138 formula feeding (FF) mothers. It was implemented in four provincial and municipal maternal and child health hospitals. The mothers’ perceptions of infant hunger cues were surveyed by self-reporting questionnaires. Chi-square tests and logistic analysis were applied to analyze the differences in maternal perceptions of infant hunger cues, including the number of hunger cues and the specific cues, between EBF group and FF group by controlling sociodemographic variables and the daily nursing indicators. Results We found that a higher proportion of EBF mothers could perceive multiple hunger cues (≥ 2) than FF mothers (66.5% vs.55.1%). For specific cues, the EBF mothers had higher perceptions of infant’s “hand sucking” (67.6% vs. 53.6%) and “moving head frantically from side to side” (34.6% vs. 23.9%), all p < 0.05. Regression analysis revealed that EBF might support mothers to perceive infant hunger cues than FF mothers, with the number of infant hunger cues (OR = 1.70, 95% CI: 1.01–2.85), “hand sucking” (OR = 1.72, 95% CI: 1.04–2.87), “moving head frantically from side to side” (OR = 2.07, 95% CI: 1.19–3.62). The number of infant hunger cues perceived by mothers was also associated with their educational level and family structure. Conclusion EBF mothers of 3-month-old infants may be more likely to perceive infant hunger cues than FF mothers in China. It is necessary to increase the health education about infant hunger and satiety cues to caregivers in China, especially among mothers with lower education levels, mothers living in nuclear families, and FF mothers.